2022
DOI: 10.26717/bjstr.2022.42.006687
|View full text |Cite
|
Sign up to set email alerts
|

"Comparison of Calcium, Chlorine, Iodine, Potassium, Magnesium, Manganese, and Sodium in Thyroid Tissue Adjacent to Thyroid Malignant and Benign Nodules"

Abstract: Thyroid Nodules (TN) are the most common endocrine disorder worldwide. Etiology and pathogenesis of thyroid benign and malignant nodules (TBN and TMN, respectively) are still not enough understood. The present study was performed to clarify the role of some Chemical Elements (ChEs) in the origination and development of TN. Contents of ChEs such as Calcium (Ca), Chlorine (Cl), Iodine (I), Potassium (K), Magnesium (Mg), Manganese (Mn), and Sodium (Na) were prospectively evaluated in thyroid tissue adjacent to TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The ratios of means and the comparison of mean values of Ag, Co, Cr, Fe, Hg, I, Rb, Sb, Sc, Se, and Zn mass fractions in pair of sample groups such as NT and TBN, NT and TMN, and also TBN and TMN is presented in Table 2. The comparison of our results with published data (from 1990 year) for I mass fraction in NT [27,28,[31][32][33][34]37,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], TBN [54,56,57,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79][80], and TMN [54,56,…”
Section: Resultsmentioning
confidence: 56%
“…The ratios of means and the comparison of mean values of Ag, Co, Cr, Fe, Hg, I, Rb, Sb, Sc, Se, and Zn mass fractions in pair of sample groups such as NT and TBN, NT and TMN, and also TBN and TMN is presented in Table 2. The comparison of our results with published data (from 1990 year) for I mass fraction in NT [27,28,[31][32][33][34]37,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], TBN [54,56,57,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79][80], and TMN [54,56,…”
Section: Resultsmentioning
confidence: 56%
“…Most often, in studies of ChE in the mammary gland, samples of visually intact tissue adjacent to the tumor are used. However, we have previously shown that the intact tissue adjacent to the thyroid tumors in terms of the level of ChE content is not identical to the normal thyroid gland tissue of apparently healthy individuals [59,60] . Therefore, in our review of reported data, only results obtained from the study of normal mammary glands of apparently healthy women were used.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the variations of published mean values for some of the studied ChE are very large and amounts to several mathematical orders. The obtained data of the studied ChE content in healthy breast tissue were compared with the reference values of the content of these ChE in blood serum [5,54] , adipose tissue [2,55] , prostate [56] and thyroid [34,[57][58][59][60] human gland (Table 4). Wherein, published data on the water content in breast tissue [61] and the results of report No.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, in studies about TE in the mammary gland, samples of visually intact tissue adjacent the tumor are used. However, we have previously shown that the intact tissue adjacent to the thyroid tumors in terms of the level of TE content is not identical to the normal thyroid gland tissue of apparently healthy individuals [53,54]. Therefore, in our review of reported data, only results obtained from the study of normal mammary glands of apparently healthy women were used.…”
Section: Discussionmentioning
confidence: 99%